2020
DOI: 10.1002/ar.24582
|View full text |Cite
|
Sign up to set email alerts
|

3D Modeling of craniofacial ontogeny and sexual dimorphism in children

Abstract: Background The range of normal variation of growth and development of the craniofacial region is of direct clinical interest but incompletely understood. Here we develop a statistical model of craniofacial growth and development to compare craniofacial ontogeny between age groups and sexes and pilot an approach to modeling that is relatively straightforward to apply in the context of clinical research and assessment. Methods The sample comprises head surface meshes captured using a 3dMD five‐camera system from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…Gender differences of size were established well before puberty and our study suggests that males experienced subtly different patterns of brain and of cranial aging as well as growth. These findings are consistent with recent work published by Smith et al (2020;Smith, Duncan, Pears, Profico & O'Higgins, 2021) as well as Milella et al (2021). We find no evidence that the aged adult cranium is more variable due to, for example, fragility nor that covariations were any weaker or stronger compared with middle aged adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Gender differences of size were established well before puberty and our study suggests that males experienced subtly different patterns of brain and of cranial aging as well as growth. These findings are consistent with recent work published by Smith et al (2020;Smith, Duncan, Pears, Profico & O'Higgins, 2021) as well as Milella et al (2021). We find no evidence that the aged adult cranium is more variable due to, for example, fragility nor that covariations were any weaker or stronger compared with middle aged adults.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier work suggests that sexual dimorphism of the anterior cranial base is established during childhood while that of the face emerges later, around puberty (Ursi, Trotman, McNamara Jr, & Behrents, 1993). More recently, Smith et al's (2020) analyses of surface landmarks has suggested that craniofacial sexual dimorphism is mostly size related and that males follow an extended growth trajectory (hypermorphosis). This size offset has also been confirmed in a recent study of skeletal landmarks (Milella, Franklin, Belcastro, & Cardini, 2021) with males, on average, more prognathic and dolichocephalic compared with females.…”
Section: Adulthoodmentioning
confidence: 99%
“…Smith et al [ 22 ] used the much larger Headspace dataset, which was used to construct the LYHM and both confirmed the above finding and also noted a second period of accelerated aging in females in the late twenties and early thirties. In a different study, but also using the same dataset, Smith et al [ 23 ] also explored changes in growth and form in children of both sexes and added to an understanding of the extent and timing of appearance of hypermorphism in the male craniofacial form.…”
Section: D M Orphable M Odelsmentioning
confidence: 99%
“…The problem of the ontogenetic origin of sexual dimorphism (SD) in mid‐facial form has been studied intensively during the last decades (Broadbent et al, 1975; Bulygina et al, 2006; Dean et al, 2000; Farkas, Posnick, & Hreczko, 1992; Farkas et al, 1992a, 1992b; Humphrey, 1998; Likus et al, 2014; Matthews, 2018; Riolo et al, 1974; Smith et al, 2021; Tutkuviene et al, 2016). Though the bulk of this research was concerned with sex‐specific growth patterns in older children and adolescents in connection to the pubertal growth spurt, it has gradually become clear that SD begins to play an important role in craniofacial variation well before puberty (Delye et al, 2015; Humphrey, 1998; Schutkowski, 1993; Ursi et al, 1993; Viðarsdottir, 1999; Wheat, 2015).…”
Section: Introductionmentioning
confidence: 99%